Exploring Secure Processing Architecture: A Comprehensive Review - Ali Arshad; Muhammad Shaan; Hafiz Muhammad Ahmed; Muhammad Iqbal (Dialogue Social Science Review (DSSR), 2025)
Secure Processing Architecture (SPA) is a fundamental paradigm in the design and implementation of computer systems aimed at safeguarding sensitive information and ensuring the integrity and confidentiality of data. In an era where cyber threats are pervasive, the need for robust security measures within processing architectures has become paramount. This abstract provides a comprehensive overview of Secure Processing Architecture, covering its key principles, components, and the methodologies employed to achieve a secure computing environment. The architecture integrates hardware and software solutions to address vulnerabilities at multiple levels, from the processor core to the overall system. The second and third section focuses on the software aspects, emphasizing the role of cryptographic protocols, secure communication channels, and secure software development practices. Secure Processing Architecture integrates cryptographic algorithms to encrypt and authenticate data, ensuring that sensitive information remains confidential and tamper-resistant. Additionally, the overview discusses the importance of isolation mechanisms within the architecture, emphasizing the need for compartmentalization to prevent unauthorized access and limit the impact of potential breaches. Virtualization technologies and containerization play a crucial role in achieving this isolation, allowing for the secure execution of multiple tasks on a single hardware platform. this abstract highlights the significance of Secure Processing Architecture in the contemporary landscape of cybersecurity. As technology continues to advance, the need for robust and adaptable security measures becomes increasingly critical. The comprehensive overview provided serves as a foundation for understanding the principles and practices associated with Secure Processing Architecture, empowering designers and developers to create resilient and secure computing systems.